How “pulaaku” moral value influence nomadic Fulani perception and non-participation in educational community development in Ikara District, Kaduna, Nigeria - Dahiru, Suleiman; Ahmad, Nobaya; Wan Jaafar, Wan Munira (Macrothink Institute, 2017)
Pastoral Fulani nomads are among the marginalized and educationally disadvantageous communities in Nigeria, and many African countries. Since education remained the mechanism for individual, community and national developments, such groups need to be given attention for the success of sustainable development goal in African nations. To achieve this, human, as well as sociocultural hindrances associated with their educational development need to be evaluated. Therefore, this study explore how pulaaku moral value influences the understanding and perception of the nomadic Fulani in education as the precipitating factor for non-participation in education in Ikara district. Two themes emerged as the findings; firstly Perception of the pastoral Fulani on education generally. Secondly factors precipitating non-participation, is presented into subthemes; strict adherence to pulaaku moral values, fear of fragmentation of social capital, lack of role model and parent ignorance. Thus, the study concluded that Fulani pastoral communities have positive perception on education, but it was evident that socio-cultural factors such as lacking role model with pulaaku principle, perception in fear of the system as a threat to social capital and ignorance influenced their low participation. Hence, there is the need for policymakers, government agencies and stakeholders to have an in-depth conceptual understanding of the Fulani values through funding ethnographic research project, and possibly integrate its ideas and those factors in the design of an acceptable nomadic education system particularly the pulaaku. Also, integrate community-based volunteer groups, purposively for advocacy and awareness will enhanced the group understanding and participation in educational community development.